2000
DOI: 10.1038/sj.onc.1203328
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the gene encoding pinin/DRS/memA and evidence for its potential tumor suppressor function

Abstract: Several cell adhesion-related proteins have been shown to act as tumor-suppressors (TS) in the neoplastic progression of epithelial-derived tumors. Pinin/DRS/memA was ®rst identi®ed in our laboratory and it was shown to be a cell adhesion-related molecule. Our previous study demonstrated that restoration of pinin expression in transformed cells not only positively in¯uenced cellular adhesive properties but also reversed the transformed phenotype to more epithelial-like. Here, we show by FISH analysis that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…Down-regulation of PNN by shRNA causes cells to become less adherent and more migratory and leads to down-regulation of several key adhesion molecules, including desmoplakin, ZO-1, and E-cadherin, which is a hallmark of neoplastic transformation (Joo et al, 2005). Consistently, PNN has been suggested to function as a tumor suppressor by studies demonstrating that PNN expression was significantly reduced in several cancer cell lines, and that exogenous PNN expression in transitional cell carcinoma-derived J82 cells led to the inhibition of anchorage-independent growth (Shi et al, 2000a). Furthermore, PNN overexpressing HEK 293 cells exhibited significant G1-S delay (Shi et al, 2001), suggesting that PNN may affect cell proliferation, and that its tumor suppressor function may not be restricted to stabilization of cell adhesion.…”
Section: Introductionmentioning
confidence: 70%
“…Down-regulation of PNN by shRNA causes cells to become less adherent and more migratory and leads to down-regulation of several key adhesion molecules, including desmoplakin, ZO-1, and E-cadherin, which is a hallmark of neoplastic transformation (Joo et al, 2005). Consistently, PNN has been suggested to function as a tumor suppressor by studies demonstrating that PNN expression was significantly reduced in several cancer cell lines, and that exogenous PNN expression in transitional cell carcinoma-derived J82 cells led to the inhibition of anchorage-independent growth (Shi et al, 2000a). Furthermore, PNN overexpressing HEK 293 cells exhibited significant G1-S delay (Shi et al, 2001), suggesting that PNN may affect cell proliferation, and that its tumor suppressor function may not be restricted to stabilization of cell adhesion.…”
Section: Introductionmentioning
confidence: 70%
“…We demonstrated that transformed cells (293 cells), which exhibit anchorageindependent growth, became anchorage-dependent upon expression of Pnn (Shi et al, 2000a). We also demonstrated that p21 cip1/waf1 levels are upregulated subsequent to increasing Pnn expression.…”
Section: Expression Of Exogenous Pnn Resulted In Activation Of the P2mentioning
confidence: 63%
“…Diminished PNN mRNA and protein levels have been documented in transitional cell and renal cell carcinomas (Shi et al, 2000a). Restoration of Pnn expression in transformed cells not only positively in¯uenced cellular adhesive properties, but also reversed the transformed phenotype of anchorageindependent growth (Ouyang and Sugrue, 1996;Shi et al, 2000a). The potential involvement of Pnn in cancer development was also suggested by aberrant expression of Pnn/DRS/memA in melanoma (Degen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations